Squamous Cell Carcinomas Confined to the Bronchial Wall: The Effect of Growth Patterns - Urer, Halide Nur; Kocaturk, Celalettin İbrahim; Gunluoglu, Mehmet Zeki; Arda, Naciye; Demir, Adalet; Ortakoylu, Mediha Gonenc; Bedirhan, Mehmet Ali; Dincer, Seyit İbrahim (The Thoracic and Cardiovascular Surgeon, 2014)
Background Squamous cell carcinomas confined to the bronchial wall (SCC-CBW) exhibit two distinct patterns of growth: superficially spreading and endobronchial mass lesions. We examined whether differences exist in the histopathological features and prognosis of SCC-CBW exhibiting different growth patterns.Materials and Methods In this study, 37 cases with SCC-CBW were included. Tumors were classified into two groups: superficially spreading squamous cell carcinoma (s-SCC) and nodular squamous cell carcinoma (n-SCC). For each case, the growth pattern, T and N status, lymphovascular and perineural invasions, immunohistochemical expressions of p53 and Ki-67, and survival rates were analyzed.Results Twenty cases were classified as s-SCC, and 17 cases were classified as n-SCC. There was a significant relationship and correlation between the length of s-SCC in the longitudinal axis and the depth of invasion (p = 0.01, R = 0.557). There was a statistically significant positive relationship between the depth of invasion and the nodal status (N1 involvement) (p < 0.0001, R = 0.71).Conclusions SCC-CBW exhibits variable growth patterns. However, despite this variability, there are no biological or histological differences between tumors of different growth patterns, and this variability has very little, if any, effect on survival.
Keywords: bronchial wall squamous cell carcinoma; histopathological features; growth pattern